Роль метаболічного синдрому в розвитку синдрому полікістозу яєчників у підлітковому віці - Авраменко, Наталія Вікторівна; Кабаченко, Олена Володимирівна; Барковський, Дмитро Євгенович; Сєрих, К. В.; Avramenko, N. V.; Kabachenko, O. V.; Barkovskyi, D. Ye.; Sierykh, K. V. (Запорізький державний медико-фармацевтичний університет, 2023)
мЗдійснили аналіз фахової літератури щодо проблеми метаболічного синдрому в дитячому та підлітковому віці, вивчили їхню роль у виникненні синдрому полікістозу яєчників (СПЯ) за останніми міжнародними керівництвами та даними наукових джерел. Актуальність проблеми обґрунтована стрімким поширенням надлишкової ваги в дітей у всьому світі і, відповідно, збільшенням частоти аліментарно-залежної патології. Одним із серйозних наслідків зайвої ваги є метаболічний синдром (МС). Нині немає чітких критеріїв МС для дітей і підлітків. IDF пропонує використовувати критерії IDF для дорослих. Пріоритет у виникненні МС віддають інсулінорезистентності (ІР), що пов’язана зі статевим дозріванням. Актуальною залишається проблема оцінювання ІР. Методи HOMA-IR і QUICKI не вважають достовірними тестами для визначення ІР, тому оцінювання ґрунтується на клінічних ознаках (гіперглікемія, дисліпідемія, абдомінальне ожиріння, гіпертонія). Ожиріння, ІР можуть бути провісниками виникнення СПЯ, який часто може бути пов’язаний із періодом статевого дозрівання. Характерні для дорослих патологічні ознаки синдрому в підлітковому віці можуть бути проявом фізіологічного перебігу статевого дозрівання. Як обов’язкові критерії для діагностики СПЯ в підлітковому віці запропоновані нерегулярні менструації / олігоменорея, доведена біохімічно та клінічно гіперандрогенемія. The review article presents an analysis of the metabolic syndrome problem in children and adolescents, its role in the development of polycystic ovary syndrome (PCOS) in accordance with the latest International guidelines and modern literature. The urgency of the problem lies in the rapid spread of overweight among children in the world and, consequently, the growth of alimentary-dependent pathology. One of the major consequences of weight problems is metabolic syndrome (MS). There are still no clear MS criteria for children and adolescents. IDF suggests using IDF criteria for adults. Priority in the pathogenesis of MS is given to insulin resistance (IR), which is associated with puberty. The problem of IR assessment remains. HOMA-IR and QUICKI methods are not considered reliable tests to determine IR, so the assessment is based on clinical signs (hyperglycemia, dyslipidemia, abdominal obesity, hypertension). Obesity and IR can be predictors of PCOS, which can often be associated with puberty. Pathological signs of the syndrome typical for adults in adolescence may be a manifestation of the physiological course of puberty. Obligative criteria for the diagnosis of PCOS in adolescence are irregular menstruation/oligomenorrhea, proven biochemically and clinically hyperandrogenemia). First-line therapy for PCOS in adolescents with MS is weight loss and dosed exercise, which helps to normalize a hormonal balance. Drug treatment may include insulin-sensitizing drugs (metformin), antiandrogens (spironlactone, flutamide, cyproterone acetate), 5-alpha-reductase inhibitors (finasteride), combined oral contraceptives, inositol. Prevention of overweight, obesity in children can prevent the development of IR and, accordingly, associated MS and PCOS, reproductive health disorders. Prevention measures are aimed at avoiding maternal obesity, gestational diabetes, malnutrition and smoking during pregnancy, promoting breastfeeding and physical activity.
The role of metabolic syndrome in the development of polycystic ovary syndrome in adolescence
Авраменко Н. В. - ORCID ID: 0000-0003-4403-2920; Кабаченко О. В. - ORCID ID: 0000-0002-8597-5362; Барковський Д. Є. - ORCID ID: 0000-0002-6806-7485; Сєрих К. В. - ORCID ID: 0000-0003-1648-7530.
Keywords: ожиріння; метаболічний синдром; синдром полікістозу яєчників; підлітковий вік; діагностика; лікування; профілактика; obesity; metabolic syndrome; polycystic ovary syndrome; adolescence; diagnosis; treatment; prevention